THE EFFECT OF FERRIS WHEEL GAMES ON MATHEMATICAL ABILITY IN EARLY CHILDHOOD: DEVELOPMENT OF COGNITIVE DIMENSIONS - Fidrayani, Fidrayani; Solehah, Aidah Siti (Journal of Early Childhood Education (JECE), 2022)
Early mathematical abilities in early childhood are a means to develop intellectual potential, mathematical thinking, and cognitive dimensions. This research was conducted on children aged 5-6 years who have not recognized mathematical concepts well and have not used the right media in learning mathematics. This study aims to test and determine the mathematical ability of children aged 5-6 years to use Ferris wheel games. The method used in the study was (SSR) using the A-B-A design. Data collection techniques are tests and observations. Early mathematical abilities in early childhood are a means to develop intellectual potential, mathematical thinking, and cognitive dimensions. This research was conducted on children aged 5-6 years who have not recognized mathematical concepts well and have not used the right media in learning mathematics. This study aims to test and determine the mathematical ability of children aged 5-6 years to use Ferris wheel games. The method used in the study was (SSR) using the A-B-A design. Data collection techniques are tests and observations. The data obtained is a score percentage processed with descriptive statistical techniques, visual data analysis, and data analysis between conditions. The study's results showed an influence on the mathematical ability of children aged 5-6 years by being proven from the percentage scores of the two subjects who increased after being given the intervention. This study concludes that the Ferris wheel game can improve children's mathematical abilities aged 5-6 years. In a wider range of objects, this game can be developed to improve mathematical skills in children.